Das Unbewusste: l’inconoscibile - Vari, Autori (Il sogno della farfalla, 2008)
The talks, delivered on the occasion of the presentation of Massimo Fagioli’s Das Unbewusste. L’inconoscibile, that brings together the lectures held at the University of Chieti during the course of 2003, highlight several of the aspects of the book itself: the relationship between the written and spoken word; the context in which the lectures were delivered, characterized by a further emphasis of the separation from psychoanalysis and organic psychiatry; the confusion that has always reigned in relation to the concept of unconscious, which the title alludes to; the history and the implications of the German word das Unbewusste; the necessity, in order to be able to offer a possibility for a the cure of a mental reality to deal with the German language and, more generally, with a language that hasn’t been able to give a name to the things that belong to the human mind.